A case of metastatic NUT carcinoma with prolonged response on gemcitabine and nab‐paclitaxel. Issue 8 (16th August 2021) - Patel, Shetal A.; Singer, Bart; Shen, Colette; Zanation, Adam M.; Yarbrough, Wendell G.; Weiss, Jared
Abstract: Background: NUT carcinoma is an aggressive malignancy characterized by translocations in the NUTM1  gene. There are currently no consensus treatment recommendations for NUT carcinomas. Methods: Here, we describe the case of a previously healthy male diagnosed with NUT carcinoma after presenting with sinus pressure, found to have a sinonasal mass and distant metastatic disease in the lungs. While pathologic evaluation and immunohistochemistry were consistent with NUT carcinoma, initial genomic profiling did not demonstrate a NUTM1 translocation. Results: Whole transcriptomic RNA sequencing of the tumor revealed a YAP1 ‐ NUTM1 fusion. Based on an in vitro drug sensitivity screen, the patient was treated with gemcitabine and nab‐paclitaxel, achieving a partial response that persisted for 9 months. Conclusions: Unbiased transcriptomic sequencing may identify previously uncharacterized NUTM1 fusion partners. Gemcitabine and nab‐paclitaxel is a well‐tolerated combination chemotherapy regimen and could offer a novel treatment approach for NUT carcinoma. Abstract : Unbiased transcriptome sequencing may identify previously uncharacterized NUTM1 fusion partners. Gemcitabine and nab‐paclitaxel is a well‐tolerated combination chemotherapy regimen and could offer a novel treatment approach for NUT carcinoma.